Inventarisasi dan Penentuan Prioritas Pembangunan Embung di Kecamatan Lamaknen Kabupaten Belu, NTT - Sulistyani, Kiki Frida; Irianto, Danang Bimo (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Lamaknen Regency is located in Belu Regency, NTT Province. This sub-district experiences water shortages during the dry season. Embung is one solution to overcome this problem. In Lamaknen District there are 5 alternative reservoir locations in 2 villages, namely Dirun Village and Makir Village. Survey activities were carried out at 5 reservoir locations to determine the condition of the watershed, the service area, and the geological conditions. From the survey results, it was found that the location with the greatest potential for inundation was the Balokama reservoir and the location with the largest watershed area of ​​the Leowalu Embung, while the one with the smallest span was the Lesutil Embung. Meanwhile, for the service area that can be two villages is the Leowalu reservoir. Kalimati and Nelas.. Survey data were then made matrices from a technical (60%) and non-technical (40%) perspective. The technical aspects consist of 9 items, namely embung span, embankment height, storage volume, distance to availability of rock and soil materials, geological conditions, access roads to the site, watershed conditions, and distance to service areas. Non-technical aspects consist of the benefits of the embung, the number of beneficiaries for irrigation, community raw water, livestock water, tourism water and the impact on the environment. From the embung matrix, it was found that Embung Nelas had the highest value, namely 80. The order of the matrix results after the Nelas reservoir was Embung Leowalu 67, Embung Kalimati 61.9, Embung Lesutil 58 and Embung Balokama 51.